Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus, dan Belanja Modal Terhadap Pertumbuhan Ekonomi(Studi Empiris di Kabupaten/Kota Eks Karesidenan Surakarta Tahun 2007-2014) - Prabowo, Intan; , Rina Trisnawati, Dra., M.Si., Akt., Ph.D (2017)
ABSTRACT This research was aimed to analyse the effect of own-source revenue, general allocation fund, special allocation fund, and capital expenditure to economic growth in distric or urban ex Surakarta from 2007 to 2014. This research used secondary data which collected from Statistic Indonesian (BPS) of Central Java and from formal website www.djpk.depkeu.go.id. Population and of sample weared at this research are distric or urban ex Surakarta amounting 7 distric or urban spanned time of year 2007-2014. the reseacrh uses multiple regression analysis method. The result of this research show that: (1) own-resource revenue has significant influence on economic growth in distric or urban ex Surakarta. (2) general allocation fund has significant influence on economic growth in distric or urban ex Surakarta. (3) special allocation fund has significant influence on economic growth in distric or urban ex Surakarta. (4) capital expenditure has no significant effect on economic growth in distric or urban ex Surakarta. Keywords: own-source revenue, general allocation fund, special allocation fund, capital expenditur, economic growth.